Pengaruh bantuan paket sembako dan bantuan langsung tunai selama pandemi Covid-19 terhadap kelangsungan hidup masyarakat - Hendra Sukmana (Publisia: Jurnal Ilmu Administrasi Publik, 2021)
The purpose of the research, one of which is to prove the effect of food package assistance and also direct cash assistance on the survival of the community during the Covid-19 pandemic. The quantitative approach is carried out using a sample of 80 respondents with multiple linear regression analysis techniques. The data collection technique is done by using a questionnaire. The results of the study indicate that first, the basic food package assistance program has a significant contribution to the survival of people's lives. Second, the cash transfer program has a significant contribution to the survival of the community. Third, the basic food package assistance program and direct cash assistance have a significant contribution to the survival of people's lives. Based on the results of research and findings in the field, the following suggestions are obtained: first, the community needs more ongoing assistance, such as employment opportunities and useful equipment assistance. to improve skills and expertise for business actors. Second, a re-evaluation of the aid distribution process is carried out so that it can be felt by the community, such as being more fair and wise in the process of collecting data on aid beneficiaries. Third, an evaluation is needed in the data collection process, where this process must prioritize deliberation from the RT to the village level, in order to obtain data that is in accordance with the value of propriety and the aspect of willingness. Based on this, the direct package assistance program and also direct cash assistance have a significant contribution to the survival of the community. Other results show that the cash transfer program has the most significant contribution in influencing the survival of the community.